ANALISIS KONFLIK MAHASISWA DAN PEMERINTAH DI INDONESIA ATAS UNDANG-UNDANG KPK DAN RUU KUHP (Pendekatan Evaluasi Manajemen Konflik dan Komunikasi Organisasi) - Alfi Syahri (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
The existence of conflict is unavoidable and will occur in the leadership process and leadership changes in it. Demonstrate that the organization needs managers, leaders, who are able to manage conflict into a joint force in building and achieving ideal goals Students and government who are directly involved in the conflict are faced with the choice to become aware of problems that are troubling the people and the government itself, the ideas of conflict resolution are emphasized in the process of mutual understanding of each party's decision making position. The goal is to unite differences in actions into a middle way to achieve common goals. Indonesia is a